Potential Neuromodulatory Profile of Phytocompounds in Brain Disorders - Luigia Trabace (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Natural and chemical compounds, often used as both dietary supplements and alternative medicines, are characterized by specific chemical properties, allowing their passage across the blood brain barrier with consequent specific effects on neurotransmission. In particular, several natural compounds have shown beneficial properties in the treatment of neuropsychiatric disorders, especially cognitive impairment and mood disorders, contributing to the maintenance of the physiological brain functioning by interacting with different receptors, transcription factors and signal transduction pathways. Neuroinflammation and oxidative stress have also been proposed as crucial contributors to brain dysfunction development, thus recent investigations have focused on novel therapeutic approaches based on the use of phytoderivates with neuroprotective properties. Thus, this Special Issue includes a collection of 11 papers, describing key findings for the identification of molecular mechanisms required for the development of potential and promising natural therapeutics for the treatment of psychiatric and neurodegenerative disorders.